2014
DOI: 10.1016/j.pupt.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo profile of aclidinium bromide in comparison with glycopyrronium bromide

Abstract: This study characterised the in vitro and in vivo profiles of two novel long-acting muscarinic antagonists, aclidinium bromide and glycopyrronium bromide, using tiotropium bromide and ipratropium bromide as comparators. All four antagonists had high affinity for the five muscarinic receptor sub-types (M1-M5); aclidinium had comparable affinity to tiotropium but higher affinity than glycopyrronium and ipratropium for all receptors. Glycopyrronium dissociated faster from recombinant M3 receptors than aclidinium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 33 publications
3
35
0
4
Order By: Relevance
“…12 Preclinical and pharmacological studies with aclidinium have demonstrated low systemic availability and a low propensity to induce cardiac arrhythmias, 11-13 and these findings have been reflected in a safety and tolerability profile that is similar to placebo in larger clinical trials. [14][15][16][17][18][19] Due to the rapid hydrolysis of aclidinium in plasma, the kidney plays little role in clearance of the drug and urinary excretion is very low.…”
Section: 10mentioning
confidence: 99%
“…12 Preclinical and pharmacological studies with aclidinium have demonstrated low systemic availability and a low propensity to induce cardiac arrhythmias, 11-13 and these findings have been reflected in a safety and tolerability profile that is similar to placebo in larger clinical trials. [14][15][16][17][18][19] Due to the rapid hydrolysis of aclidinium in plasma, the kidney plays little role in clearance of the drug and urinary excretion is very low.…”
Section: 10mentioning
confidence: 99%
“…Nevertheless, we are confident that investigations performed on healthy preparations can provide useful insights into the regulation of the cough reflex as well as hints for further studies on this reflex and possibly for the development of novel antitussive strategies. Preclinical studies have indicated that aclidinium may have a faster onset of action than tiotropium, but comparable protective effects on bronchoconstriction [32,33]. In addition, since it has been reported that the clinical dose of tiotropium 18 mg is very low with respect to the clinical dose of aclidinium 400 mg [14], we made an attempt to find the isoeffective dose of the two drugs as far as bronchodilation is concerned.…”
Section: Methodological Considerations and General Remarksmentioning
confidence: 99%
“…In addition, since it has been reported that the clinical dose of tiotropium 18 mg is very low with respect to the clinical dose of aclidinium 400 mg [14], we made an attempt to find the isoeffective dose of the two drugs as far as bronchodilation is concerned. The potency of these two LAMAs has been previously assessed in guinea pigs [32,33]. Aclidinium 100 mg/mL and tiotropium 10 mg/mL produced 1 h post-administration equi-effective (97e98%) inhibition of acetylcholine-induced bronchoconstriction that lasted several hours.…”
Section: Methodological Considerations and General Remarksmentioning
confidence: 99%
See 2 more Smart Citations